Pengaruh Nilai Tukar Rupiah (Kurs), Jakarta Islamic Index (JII), Usia Reksadana dan Volume Perdagangan Reksadana Terhadap Nilai Aktiva Bersih (Nab) Reksadana Campuran Syariah - Sarah Chairani (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to determine the effect of the exchange rate of the rupiah (the exchange rate), the Jakarta Islamic Index (JII), the age of the mutual fund, the volume of mutual fund trading on the net asset value of mixed sharia mutual funds registered at the Financial Services Authority (OJK). The sampling technique used was judgment sampling with a selected sample of 6 (six) syariah mixed mutual funds. The type of data used is secondary data. Data analysis using SPSS 25. Data collection techniques in this study used document review, which is data collection carried out by examining the company's 2013-2018 financial statements. The results of the data analysis show that partially the exchange rate, Mutual Fund Age, and Trading Volume have a significant effect on the value of net assets, whereas JII partially has no significant effect on the value of net assets. Simultaneously shows the Exchange Rate, JII, Mutual Fund Age, and Trading Volume significantly influence the net asset value. Keywords : Rupiah Exchange Rate (Kurs), Jakarta Islamic Index (JII), Age Fund, Trading Volume, Net Value Assets (NAV).